A CASE OF SPONTANEOUS REGRESSION OF IDIOPATHIC BILATERAL ADRENAL HEMORRHAGE IN A MIDDLE AGED WOMAN: 1 YEAR FOLLOW-UP - Song, Y.W. (Acta Endocrinol (Buchar), 2016)
BACKGROUND: Bilateral adrenal hemorrhage is a serious condition that can result in adrenal insufficiency, shock, acute adrenal crisis, and mortality if it is not managed with adequate treatment. We report a rare case of idiopathic bilateral adrenal hemorrhage. CASE PRESENTATION: A 50-year-old woman visited our hospital with complaints of right upper abdominal pain. A computed tomography (CT) revealed unilateral left adrenal gland hemorrhage. However, the results of rapid adrenocorticotropic hormone (ACTH) stimulation test and adrenomedullary hormone function test were normal. Since the patient did not show signs of adrenal insufficiency, corticosteroid therapy was postponed and only supportive management therapy was started. After 1 week, a follow- up CT showed a previously unseen adrenal hemorrhage on the right adrenal gland, but the rapid ACTH stimulation test result was normal. One year later, no hemorrhagic signs were observed on the follow-up CT. CONCLUSION: In most cases of idiopathic bilateral adrenal hemorrhage, patients are treated with steroid replacement therapy due to adrenal insufficiency. In some other cases, patients are treated with steroids despite the absence of adrenal insufficiency. Here we reported a very rare case of idiopathic bilateral adrenal hemorrhage sequentially to emphasize that before initiation of adrenal hormone replacement therapy, it is important to determine whether adrenal insufficiency is present. If there is no evidence of adrenal insufficiency, adrenal replacement therapy should be postponed until the presence of adrenal insufficiency is confirmed.